EFP Delphi study on the trends in Periodontology and Periodontics in Europe for the year 2025. (10th May 2016) - Madianos, Phoebus; Papaioannou, William; Herrera, David; Sanz, Mariano; Baeumer, Amelie; Bogren, Anna; Bouchard, Philippe; Chomyszyn‐Gajewska, Maria; Demirel, Korkud; Gaspersic, Rok; Giurgiu, Marina; Graziani, Filippo; et al.
Abstract: Aim: The aim was to assess the potential trends in Periodontology and Periodontics in Europe that might be anticipated by the year 2025, using the Delphi method. Material and Methods: The expert opinion of 120 experts was sought through the use of an open‐ended questionnaire, developed by an advisory group, containing 40 questions concerning the various trends in periodontology. Results: The experts (113 responders) expect a stabilization of the prevalence of periodontitis, both for the chronic as well as the aggressive cases, but an increase in implant‐related diseases up to the year 2025. Concurrently, the importance of implants is seen to be increasing. They foresee an increased demand for postgraduate periodontology and implantology training. This is mirrored in an increase in publications for implant dentistry and increase in demand and need for training. Concerning the patients, better‐informed individuals seeking more routine check‐ups are expected. Conclusion: A continued need for specialized periodontists, but also well trained dental practitioners is foreseen for next decade in Europe. Apart from periodontology they will be increasingly exposed to and trained in implant dentistry.